Low avidity circulating SARS-CoV-2 reactive CD8+ T cells with proinflammatory TEMRA phenotype are associated with post-acute sequelae of COVID-19 - Paniskaki, Krystallenia; Konik, Margarethe J.; Anft, Moritz; Heidecke, Harald; Meister, Toni L.; Pfaender, Stephanie; Krawczyk, Adalbert; Zettler, Markus; Jäger, Jasmin; Gaeckler, Anja; Dolff, Sebastian; Westhoff, Timm H.; et al. (Frontiers in Microbiology, 2023)
The role of adaptive SARS-CoV-2 specific immunity in post-acute sequelae of COVID-19 (PASC) is not well explored, although a growing population of convalescent COVID-19 patients with manifestation of PASC is observed. We analyzed the SARS-CoV-2-specific immune response, via pseudovirus neutralizing assay and multiparametric flow cytometry in 40 post-acute sequelae of COVID-19 patients with non-specific PASC manifestation and 15 COVID-19 convalescent healthy donors. Although frequencies of SARS-CoV-2-reactive CD4+ T cells were similar between the studied cohorts, a stronger SARS-CoV-2 reactive CD8+ T cell response, characterized by IFNγ production and predominant TEMRA phenotype but low functional TCR avidity was detected in PASC patients compared to controls. Of interest, high avidity SARS-CoV-2-reactive CD4+ and CD8+ T cells were comparable between the groups demonstrating sufficient cellular antiviral response in PASC. In line with the cellular immunity, neutralizing capacity in PASC patients was not inferior compared to controls. In conclusion, our data suggest that PASC may be driven by an inflammatory response triggered by an expanded population of low avidity SARS-CoV-2 reactive pro-inflammatory CD8+ T cells. These proinflammatory T cells with TEMRA phenotype are known to be activated by a low or even without TCR stimulation and lead to a tissue damage. Further studies including animal models are required for a better understanding of underlying immunopathogensis.